2016
DOI: 10.1042/bsr20160075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of serum amyloid A on the structure and antioxidant ability of high-density lipoprotein

Abstract: Serum amyloid A (SAA) levels increase during acute and chronic inflammation and are mainly associated with high-density lipoprotein (HDL). In the present study, we investigated the effect of SAA on the composition, surface charge, particle size and antioxidant ability of HDL using recombinant human SAA (rhSAA) and HDL samples from patients with inflammation. We confirmed that rhSAA bound to HDL3 and released apolipoprotein A-I (apoA-I) from HDL without an apparent change in particle size. Forty-one patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 29 publications
7
33
0
Order By: Relevance
“…Although the anti-oxidant effect of apoA-I on LDL is well-established, to our knowledge this is one of the first reports of a similar, but smaller, effect of free SAA on LDL (Fig. 4B), along with a very recent study by Sato et al (24) reporting that SAA decelerates copper-induced LDL oxidation. Both our study and the study by Sato et al also show that SAA decelerates copper-induced HDL oxidation in a dose-dependent manner ( Figs.…”
Section: Free Saa Delays Ldl Lipid Peroxidation By Coppersupporting
confidence: 67%
See 1 more Smart Citation
“…Although the anti-oxidant effect of apoA-I on LDL is well-established, to our knowledge this is one of the first reports of a similar, but smaller, effect of free SAA on LDL (Fig. 4B), along with a very recent study by Sato et al (24) reporting that SAA decelerates copper-induced LDL oxidation. Both our study and the study by Sato et al also show that SAA decelerates copper-induced HDL oxidation in a dose-dependent manner ( Figs.…”
Section: Free Saa Delays Ldl Lipid Peroxidation By Coppersupporting
confidence: 67%
“…In this work, we determined the combined effects of SAA enrichment and oxidation by various oxidative agents on the biochemical and biophysical modifications in HDL and LDL, with the main focus on HDL. Concurrently, Sato et al (24) reported, for the first time, that human SAA retards the copper-induced oxidation of HDL and LDL. Together, these results indicate that SAA partially compensates for the loss of anti-oxidant HDL proteins, suggest a new physiological function for SAA as a mild anti-oxidant for lipids, and shed new light on the complex role of SAA in lipid oxidation and human disease.…”
Section: Preparation and Characterization Of Saa•hdlmentioning
confidence: 90%
“…Under inflammatory conditions, SAA displaces ApoA-I, the predominant apolipoprotein of HDL. Although debated in the literature [23,55], at least some of the available data [56][57][58] indicate that this mode of ApoA-I displacement alters HDL function and effectively promotes a pro-atherogenic phenotype at a threshold when SAA constitutes more than half of the HDL protein [59]. Therefore, it is hypothesized that the ratio of SAA/HDL is important for HDL anti-inflammatory and antioxidant activities in biological systems.…”
Section: Discussionmentioning
confidence: 99%
“…HDL also inhibits SAA-mediated reactive oxygen species generation and Nod-like receptor protein 3 (NLRP3) inflammasome activation [22]. Nonetheless, others have reported contradictory results showing that reconstituted HDL containing SAA showed higher antioxidant potential than normal HDL [23] and that SAA bound by HDL exhibited no discernible cytotoxicity under pathophysiological conditions [24].…”
Section: Introductionmentioning
confidence: 99%
“…54 HDL cell-cholesterol efflux capacity (CEC) has been inversely linked to ASCVD. [64][65][66] The primary methods of cell-cholesterol efflux are via ABCA1 and scavenger receptor class B type I (SR-BI). 67 Studying the activity of these has allowed for a better understanding of cholesterol transport.…”
Section: Endothelial Cell Macrophages/monocytes and Other Cell Typesmentioning
confidence: 99%